Обмежувач струму короткого замикання з надпровідною обмоткою - Данько, В.Г.; Гончаров, В.Г. (Електротехніка і електромеханіка, 2012)
In the article, a fault current limiter with a superconducting winding is considered, a method of its main parameters calculation offered.